Ecclesiology and evangelism in the catholic tradition of the Church of England claiming the future from the past - Warner, Martin 1940- (2018)
This article considers the relationship between ecclesiology and evangelism in the catholic tradition of the Church of England, following the Tractarian revival in the nineteenth century. It seeks to draw conclusions from the effects of that revival, identifying the origin, in theological conviction, of important developments such as the restoration of religious communities. One of the qualities of this application of theology to apostolic practice is its subversive effect on the settled, and limited, expectations of the Church of England, and on society at large. However, it is also stressed that this subversion is not destructive; rather it is a manifestation of the scandal of the cross and the wisdom of God that confounds worldly expectations. This survey of the subversive impact of the Tractarian revival also considers the implications of its achievements for those who are the inheritors today of that creative theological and evangelistic ferment. Today in the Church of England, those who hold to a discipline of admission to ordination that is consistent with the historic practice of the ancient traditions in eastern and western Christendom are generally referred to as traditional catholics. In the present theological climate that term can be regarded by many as suggesting little more than resistance to change. This article seeks to recover the sense that tradition, properly lived, is itself subversive in ways that fruitfully reveal the ever ancient and ever new character of God's self-revelation.
Keywords: Ecclesiology; Jeremy Paxman; Richard Hooker; Catholic Tradition; Evangelism; Scripture; subversiveness of tradition; the Tractarian revival; tradition and reason